2012
DOI: 10.1111/j.1365-2400.2012.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of harvest and minimum size limit regulations for controlling short‐term harvest in recreational fisheries

Abstract: It is important to consider the potential effectiveness of regulations for reducing total harvest levels when developing fishery management plans. A random forest (RF) modelling approach was used to examine how changing per‐angler harvest or minimum size limit regulations affected sport fishery harvest in US Atlantic coast recreational fisheries. Harvest limits per angler (i.e. bag limits) were typically high initially and subsequently reduced, whereas almost half of minimum length limits were initially below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The low proportion of anglers who reached the official harvest limits (15 kg plus one fish) reflects the ineffectiveness of this regulation when the initial quota is large and/or is implemented in areas where fishing effort is still unrestricted (Van Poorten et al . ). According to Van Poorten et al .…”
Section: Discussionmentioning
confidence: 97%
“…The low proportion of anglers who reached the official harvest limits (15 kg plus one fish) reflects the ineffectiveness of this regulation when the initial quota is large and/or is implemented in areas where fishing effort is still unrestricted (Van Poorten et al . ). According to Van Poorten et al .…”
Section: Discussionmentioning
confidence: 97%
“…Post's (2013) opinion, 10 years after publishing the highly cited 'invisible collapse' article (Post et al 2002), was that many agencies and anglers still did not believe that angling mortality could drive fish populations to collapse, defined as population size reductions to <10% of virgin biomass. Van Poorten et al (2013) analysed the harvest-reduction effect of marine recreational fisheries regulations in the USA, and similarly noted that restrictive minimum-size limits would be needed to reduce harvest notably, while other harvest restrictions (e.g. Allen et al (2013) supported this conclusion by showing that unresponsive fishing effort, which essentially mimicked a situation where angler satisfaction was not only determined by catch rate or size of fish but also be non-catch factors such as travel distance, required reasonably high minimum-size limits or other harvest constraints to avoid recruitment overfishing.…”
Section: Towards Resilient Recreational Fisheries On a Global Scalementioning
confidence: 99%
“…Models, however, have shown that such sharp declines are indeed conceivable, even at realistically low levels of fishing effort (Hunt et al 2011). daily bag limits) were ineffective Van Poorten et al 2013). Van Poorten et al (2013) analysed the harvest-reduction effect of marine recreational fisheries regulations in the USA, and similarly noted that restrictive minimum-size limits would be needed to reduce harvest notably, while other harvest restrictions (e.g.…”
Section: Towards Resilient Recreational Fisheries On a Global Scalementioning
confidence: 99%
“…; Radomski ; van Poorten et al . ). Fishery management rules are applied equally to both skilled and unskilled anglers, but contribute to catch inequality because of the greater innate efficiency that skilled anglers have and because very few anglers catch their bag limit (Baccante ; Cook et al .…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that inequality in catch distribution can be explained by chance (Thompson ; Alvarez & Schmidt ; Seekel ), the type of fishing tackle used (Baccante ), fisheries management actions (Baccante ; van Poorten et al . ) and fish abundance (Bannerot & Austin ). However, fish abundance is not easy to measure, so catch‐per‐unit‐effort (CPUE) – which is assumed to be proportional to population size (Quinn & Deriso ) – has often been used to explore inequalities in catch distribution.…”
Section: Introductionmentioning
confidence: 99%